Hematoma duodenal intramural. Presentación de un caso. - Lechuga Farías, Hernán; García Suárez, Manuel; Montejo Otero, Marcelino; Urbizo Cañón, Miguel (Revista Cubana de Pediatría, 2023)
Presenta el caso de hematoma duodenal itramural.